COVID-19 pandemic: a narrative review on legislative and regulatory framework in India for disaster and epidemic - Sahoo, Durgesh Prasad; Alekhya, G.; Bhatia, Vikas; Parida, Swayam Pragyan (International Journal of Research in Medical Sciences, 2020)
Public health legislation plays an important role in the containment of any epidemic or pandemic. During a pandemic, it might be necessary to override the existing laws or (individual) human rights for the containment of the pandemic. The objective of the study is to review the legal framework pertaining to COVID-19 pandemic preparedness in India. This study has been done as an unsystematic narrative review where various legislations were assembled from electronic data base, websites from various legislative and Ministries and discussion with experts. Owing to contain the spread of the novel coronavirus Government of India announced nationwide lockdown on 24th March, 2020. For proper implementation of lockdown measures various legislative laws belonging to different ministries is required. There are two pioneer acts namely The Epidemic disease act of 1897 and The Disaster management act of 2005. Under these two acts the government has laid down various rules and regulations that have to be followed during lockdown. This article describes the need for the law in a crisis like this and various legislations that have been implemented during lockdown.